Suspended While Black in Majority White Schools: Implications for Math Efficacy and Equity. Issue 1 (21st December 2021) - Johnson, Odis; Jabbari, Jason
Abstract: This article explores whether racial disparities in mathematics arise in majority White schools for students who receive in-school suspensions (ISS). Using data from the High School Longitudinal Survey and machine learning generated propensity scores to estimate average treatment effects, we find Black suspended students in schools with low White enrollment have math test scores and efficacy beliefs no different than non-suspended Black students, but experience declines in their math scores as the percentage of White enrollment increases.